1996
DOI: 10.1016/s0006-3495(96)79708-4
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of plant cell walls by atomic force microscopy

Abstract: Atomic force microscopy has been used to visualize the ultrastructure of hydrated plant cell wall material from prepared apple (Malus pumila MILL; Cox orange pippin), water chestnut (Eleocharis dulcis L.), potato (Solanum tuberosum L.; Bintje), and carrot (Daucus carota L.; Amsterdamse bak) parenchyma. Samples of cell wall material in aqueous suspension were deposited onto freshly cleaved mica. Excess water was blotted away and the moist samples were imaged in air at ambient temperature and humidity. The three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
68
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(74 citation statements)
references
References 27 publications
3
68
2
1
Order By: Relevance
“…AFM images are the result of convolutions of the tip and the "true" structure of the specimen at an atomic resolution. Plant cell walls were one of the first biological samples that were examined by AFM (Kirby et al, 1996;van der Wel et al, 1996). The motivation of using AFM for characterizing cell walls is obvious: plant cell walls are relatively stiff and flat, and the molecular features of the microfibril network occur at the nanometer scale.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…AFM images are the result of convolutions of the tip and the "true" structure of the specimen at an atomic resolution. Plant cell walls were one of the first biological samples that were examined by AFM (Kirby et al, 1996;van der Wel et al, 1996). The motivation of using AFM for characterizing cell walls is obvious: plant cell walls are relatively stiff and flat, and the molecular features of the microfibril network occur at the nanometer scale.…”
mentioning
confidence: 99%
“…The motivation of using AFM for characterizing cell walls is obvious: plant cell walls are relatively stiff and flat, and the molecular features of the microfibril network occur at the nanometer scale. Ideally, AFM could be used to answer some of the key questions regarding the nanostructures within plant cell wall cellulose (Kirby et al, 1996;van der Wel et al, 1996;Engel et al, 1999;Morris et al, 1999;Thimm et al, 2000;Davies and Harris, 2003) beyond that defined by the previously mentioned analytical techniques.…”
mentioning
confidence: 99%
“…(103) In this seminal study, it was demonstrated for the first time that AFM could be used to effectively image and study the structural arrangement of cellulose within partially hydrated plant cell walls ( Figure 5). The topographical and error AFM images obtained from the cell wall of different plant species showed layers of aligned fibrous structures, which on the basis of size and shape were taken to be cellulose microfibrils.…”
Section: Elucidation Of Cellulose Structure and Biochemical Compositionmentioning
confidence: 99%
“…To assess the ultrastructural alterations caused in the cell wall by FESEM, we compared cell walls prepared for FESEM to those imaged with atomic force microscopy (AFM). AFM has been used to investigate cell wall ultrastructure but mostly on cell walls that have been homogenized rather than in intact tissue [3,4].For material, from the hypocotyls of dark-grown cucumber (Cucumis sativus), we examined cortical parenchyma, which are large and relatively uniform cells, and in which the wall surface is exposed by bisecting the hypocotyl in water. Samples for AFM were imaged in air on Nanoscope III (Digital Instruments).…”
mentioning
confidence: 99%
“…To assess the ultrastructural alterations caused in the cell wall by FESEM, we compared cell walls prepared for FESEM to those imaged with atomic force microscopy (AFM). AFM has been used to investigate cell wall ultrastructure but mostly on cell walls that have been homogenized rather than in intact tissue [3,4].…”
mentioning
confidence: 99%